Jednolity rynek energii: konwergencja czy utrzymywanie status quo - Dobroczyńska, Agnieszka; Juchniewicz, Leszek (Internal Energy Market: Convergence or Status Quo?, 2008)
The subject of this working paper is the evolution of the energy sector and scope of activities that from national energy markets via regional initiatives lead towards the Internal Energy Market. It has been for 10 years that the determined efforts in the political and legal spheres have been taken to liberalize and integrate national electricity and gas markets, though with poor positive effects. The previous statement is a starting point to diagnose and bring into order various reasons - out of the energy area - of the present state and on that basis to set the perspective that helps to reach the Lisbon Strategy aims. In this context the European Energy Policy is a prerequisite, the fixed imperative of which is spreading of competition that brings benefits to energy consumers (economic dimension of the cohesion). However, it does not mean that common and uniform European Energy Policy should replace national energy policies. In many cases decisions should be taken exclusively on the member states' level according to the subsidiarity rule (i.e. usage of nuclear).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 293-304